Regulatory consideration on preparation and clinical use of COVID-19 convalescent plasma. (October 2020) - Yılmaz, Soner; Ertuğrul Örüç, Nigar; Özcebe, Osman İlhami and Azap, Alpay and Çetin, Ahmet Türker and Yenicesu, İdil and Öztürk, Abdullah and Gündüz, Mehmet and Tekin, Ahmet
Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the cause of coronavirus disease (COVID-19), spreading from Wuhan to worldwide has been emerged since December 2019. Although scientists and researchers have been racing to develop specific therapeutic agents or vaccines against SARS-CoV-2 since the identification of the agent, either a drug or a vaccine has not been approved to treat or to prevent COVID-19 up to date. On the base of historical experiences, Convalescent Plasma (CP), a passive antibody therapy, has been evaluated as a hopeful and potential therapeutic option since the beginning of the COVID-19 outbreak. Immune plasma had been used previously for the treatment of H1N1 influenza virus, SARS-CoV-1 and MERS-CoV epidemics successfully. In this scope competent authorities are responsible to set up certain principles and criteria for the collection and clinical use of COVID-19 Convalescent Plasma (CCP). This document has been prepared to aid both for the convalescent plasma suppliers and the clinicians. The first part encompasses the supply of CCP and the second part lead the clinical use of CCP for the treatment of patients with severe COVID-19 infection. Turkish Ministry of Health developed a guide on collection and clinical use of CCP and created a web-based monitoring system to follow-up the patients treated with convalescent plasma in universal. This follow-up process is thought to be crucial for the creation and development of current and future treatment modalities. This guide would be a pathfinder for clinicians and/or institutions those eager to conduct CCP treatment more effectively.